Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have $E(X|Y,Z)=0$, $X$ independent of $Y$ and of $Z$ and I want to conclude that $E(X)=0$ ($X,Y,Z$ are real-valued random variables). Okay it seems quite obvious, but if I try to make a strict argument I find a missing step.

I tried to approach this from both sides:

  • From the independence follows, that $X$ is independent of $\sigma(Y) \cup \sigma(Z)$.

  • The first expression is, more exactly $=E(X| \sigma(Y,Z))$. $\sigma(Y,Z)=\sigma(\sigma(Y) \cup \sigma(Z))$.

It is known, that in general $\sigma(\mathcal{A} \cup \mathcal{B}) \neq \mathcal{A} \cup \mathcal{B} (*)$ for $\sigma$-algebras $\mathcal{A}, \mathcal{B}$. Question: How can I conclude $E(X)=0$ anyway?

Maybe for independent random variables the equality $(*)$ does hold? Or there is m maybe an alternative, more convenient expression for conditional expectations on more than one random variables?

share|cite|improve this question
For every integrable random variable X and every sigma-algebra G, one of the two defining properties which characterize Y=E(X|G) is that E(X;A)=E(Y;A) for every A in G (you know the other one). Use this for A=Omega. – Did Aug 4 '11 at 12:48
up vote 3 down vote accepted

Elaborating on the comment by Didier Piau. You don't even need an independence, since it's just simply a "tower rule": $$ \mathsf E[\mathsf E[X|\mathcal F]] = \mathsf EX $$ under some conditions on the integrability. In your simple case by the definition of the conditional expectation you have $$ \mathsf E[\eta\cdot \mathbf 1_A] = \mathsf E[X \mathbf 1_A] $$ if $A\in \sigma(Y,Z)$. Here $\eta = \mathsf E [X|Y,Z]$.

You know from the definition of $\sigma$-algebra that $\Omega\in \sigma(Y,Z)$ so $\mathbf 1_\Omega = 1$ and you have $$ 0 = \mathsf E[\eta] = \mathsf E[X] $$

Edited: answering your last comment. First, an example which justifies your intuition. Let $$ X = \begin{cases}1,\quad p=0.5,\\ 0,\quad p = 0.5.\end{cases} $$ and $A\subset\Omega = \{X = 0\}$, $\mathsf P(A) = 0.5$. By the definition of conditional expectation we have $$ \mathsf E[X|A] = \int\limits_\Omega X(\omega)\mathsf P(d\omega|A) = \frac{1}{\mathsf P(A)}\int\limits_A X(\omega)\mathsf P(d\omega) = 0 $$ while $\mathsf E[X] = 0.5$.

On the other hand, let us consider the random variable $\xi = \mathbf 1_A$. Clearly, $\mathcal F_\xi = \{\emptyset,A,A^c,\Omega\}$ and you would like to have the same result as before. But there is a slightly difference. $$ \mathsf E[X\mid\mathcal F_\xi] = 1-\xi $$ and we cannot say that $1-\xi = 0 \quad\mathsf P$-a.s. That's way you don't have that $\mathsf E[X] = \mathsf E[X\mid\mathcal F_\xi] = 0$.

Roughly speaking, the condition $\mathsf E[X\mid \mathcal F_\xi] = 0$ says that it will hold independently of the value of $\xi$ - so in all cases which can be characterized by $\xi$.

share|cite|improve this answer
very nice, clear argument – Johannes L Aug 5 '11 at 7:41
On a second thought, this shows that $E(X | \mathcal{F})=0$ implies $E(X)=0$ and it seems counter-intuitive to me, if I view the first expression as the expectation given the "information" in $\mathcal{F}$ and in the second I don't consider that "information". How would you interpret the result? – Johannes L Aug 5 '11 at 8:38
@Johannes L: here you are. – Ilya Aug 5 '11 at 9:02

See law of total expectation: $$ E(E(X \mid Y)) = E(X). $$ So that does it.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.